Locally invasive melanoma in the internal laminae of the hoof of a bay mule. (13th May 2018) - Kay, G.; McNeil, P.; Knottenbelt, D.; Tligui, N.
Summary: An 8‐year‐old bay mule was presented with moderate right forelimb lameness and dark discolouration of the white line. Histopathology of the dark material indicated a melanoma. Extensive resection and debridement were not curative and the mule was subjected to euthanasia 70 days after presentation.